Pemberdayaan Masyarakat Pedagang Kaki Lima di Sekolah Terdampak Covid-19 di Kecamatan Way Jepara Kabupaten Lampung Timur - Sumaryati; Hanna Hilyati Aulia (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2021)
This paper aims to describe the empowering of street vendors in schools affected by covid-19 in Way Jepara District, East Lampung Regency. This article uses a participatory action research approach in the process of empowering street vendors. The results of this research are as follows: Assistance of street vendors has changed, namely; First, the increased self-awareness of traders that entrepreneurship must be started now and be tried immediately so that they can become independent; Second, being able to make changes to the way of organization to be of higher quality; Third, the formation of a merchant gathering forum with the name Fosikom Kreatif PKL Way Jepara as a forum for empowering traders who according to them can provide solutions in a pandemic situation. After this action research program was carried out, the street vendors in Way Jepara District, had the skills and activities that could meet the daily needs of their families to create a safe, peaceful, prosperous and harmonious society.